PENGARUH FAKTOR SISTEMATIS DAN NON SISTEMATIS TERHADAP RISIKO INVESTASI SAHAM SEKTOR INDUSTRI BARANG KONSUMSI DI PT BURSA EFEK INDONESIA - Ni Komang Ayu Nuriyani; I Gusti Ngurah Bagus Gunadi; I Wayan Suarjana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2021)
This study aims to determine the effect of systematic factors as well as the influence of non-systematic factors on the risk of stock investment in the Consumer Goods Industry sector in PT. Indonesia Stock Exchange for the period 2016-2018. Sampling was carried out by purposive sampling method with the criteria for companies in the Consumer Goods Industry sector which are listed on the Indonesia Stock Exchange and have complete financial reports for the period 2016 to 2018. Data analysis techniques use multiple linear regression analysis, analysis of the coefficient of determination, partial regression test (test t), and simultaneous parisal regression test (f test) where the results of the linear regression test performed produce the equation The results of this study indicate that the partial test results with alpha (α) 0.5 that inflation with a significant value of 0.785 and IHSG with a significant value of 0.705 which is greater than the degree of error of 5% (0.05) has no significant effect on risk. Meanwhile, other variables such as Company Liquidity with a significant value of 0.000, financial leverage with a significant value of 0.397 and ROE with a significant value of 0.030 have a value smaller than the degree of error of 5% (0.05) which has a significant effect on investment risk. stock. Simultaneously, all independent variables have a significant effect on the dependent variable because the significant value of all variables is less than the degree of error, namely 0.000 (0.000 <0.05). From the results of the determination test, it was obtained an adjusted R square value of 0.365 or 36.5%, which means that the ability to vary the independent variables (X1, X2, X3, X4, X5) simultaneously to explain the variation in the dependent variable (Y) is 36.5% while 63.5% of the variation in the dependent variable (Y) is explained by other variables which are not analyzed